Perspectives on human and social capital theories and the role of education: An approach from Mediterranean thought. Issue 14 (6th December 2018) - López Castellano, Fernando; García-Quero, Fernando; García-Carmona, Marina
Abstract: Current discussions about education suggest that a transformative pedagogy that goes beyond the acquisition of knowledge and skills is needed. However, there is no agreement as to the inputs needed for a correct development of the educational model. In this sense, we can identify the presence of two different approaches to human and social capital which embody distinct educational worldviews. On the one hand, the 'Marketable Human Capital' or 'Personal Culture' approach, and on the other hand, the 'Non-Marketable Human Capital' or 'Civic Culture' approach. The first, which is linked to mainstream economic theory, sees education as any stock of knowledge that contributes to an improvement in the productivity of the worker and individual well-being. The second, which is rooted in the Mediterranean tradition of political thought, highlights the role of civic virtues, reciprocity, and public action within the educational process and its influence on public happiness. In this article, we analyse these connections in order to introduce the eighteenth-century Mediterranean tradition of economic thought into discussions about human and social capital theories and the role of education in them. Focusing on education through these prisms, national and international agendas must be reoriented towards the integral development of people to include broader global debates. Abstract :